Pengaruh Kepemimpinan dan Budaya Organisasi terhadap Kepuasan Kerja dan Kinerja - Septherine, Putri; Zulfadil, Zulfadil; Samsir, Samsir (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The purpose of this research is to determine the influence of leadership and organizational culture on job satisfaction and performance. This type of research is quantitative descriptive research. This research was carried out at Prima Pekanbaru Hospital. The population in this study was all nursing staff who worked in 7 inpatient rooms at Prima Pekanbaru Hospital, totaling 302 people. The number of samples taken in this study was 75 nursing staff who served in 7 inpatient rooms at Prima Pekanbaru Hospital. Data analysis uses the Partial Least Square (PLS) approach. The research results show that leadership has a positive effect on job satisfaction. Organizational culture has a positive effect on job satisfaction. Leadership has a positive effect on nurse performance. This means that having visionary leadership who dares to take risks in every decision made will provide an increase in nurse performance. Organizational culture has a positive effect on nurse performance. Job satisfaction has a positive effect on nurse performance. Job satisfaction has a positive effect on leadership and performance.